The effect of ethanol extract of fruit peel jengkol (Archidendron pauciflorum) to spleen histological structure of streptozotocin-induced diabetic rats (Rattus norvegicus) - DESAK MADE MALINI; Selma Alamanda Abadi; MADIHAH; WAWAN HERMAWAN (Smujo International, 2019)
Abstract. Malini DM, Abadi SA, Madihah, Hermawan W. 2019. The effect of ethanol extract of fruit peel jengkol (Archidendron pauciflorum) to spleen histological structure of streptozotocin-induced diabetic rats (Rattus norvegicus). Nusantara Bioscience 11: 157-161. Diabetes Mellitus (DM) is a chronic endocrine disorder associated with several secondary complications. The spleen is a lymph organ with the main function of filtering red blood cells, immune response and playing any kind of role in diabetes. Despite the currently available anti-diabetic drugs, there are need remedies for alternatives which are economical and safe. One alternative medicine well known by local Indonesian communities to treat DM is the fruit peel of Archidendron pauciflorum. This study aimed to evaluate the histological changes in the spleen following administration of ethanol extract of fruit peel Archidendron Pauciflorum (EEJFP) in the streptozotocin (STZ) - induced diabetic rats. Diabetic rats were used in this study consisting of six groups of four animals each. The treatments given are NC (CMC solution 0.5%), Positive Control (CMC solution 0.5%), G (glibenclamide), Treatment 1, 2, and 3 (EEJFP dose 385; 770; 1540 mg/kg bw). All of the treatment was administered orally to the experimental rats 14 days following induction. The spleen was collected and the histological study was performed using hematoxylin and eosin (H&E). The parameters observed were the number of necrosis and cell damage score, including fat degeneration, hydropic degeneration, and inflammatory cell. The result showed that EEJFP at dose 385 mg/kg bw and 770 mg/kg bw gave significant recovery (p<0.05) on spleen damage by the decreased of the number of necrotic cells and cell damage score which lower than other treatments and compared to negative control group. It was concluded that doses of 385 mg/kg bw EEJFP are the optimum dose to improve the histological structure of spleen damage in diabetic rats.